Human Rights Thought: Between Islamic Law and The Universal Declaration of Human Rights - Deviana Yuanitasari; Kusmayanti, Hazar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The issue of human rights among Muslim countries is nothing new. Islamic Shari'a which is universal explains a lot of basic principles regarding equality of human rights and freedoms, even when the Prophet Muhammad declared the Medina Charter. The history of the enactment of Islamic law among Muslim communities has shifted from a vertical normativity point to a horizontal one. This is because the development of the enactment of Islamic law has also been influenced by socio-cultural dynamics and legal politics in Islamic society itself. Islam has first taught mankind about the concept of egalitarianism, universalism and democracy. This beautiful and comprehensive concept is allegedly adopted by the West through the emergence of universal ideas which are standardized in the Universal Declaration of Human Rights convention. Islam is an ash-Syumul religion. Islamic teachings cover all aspects of human life. Islam provides regulations and demands on humans, ranging from the smallest affairs to large-scale affairs. And of course, it includes rules and high respect for human rights (HAM). However, it is not in one structured document but is spread out in the holy verses of the Koran and the Sunnah of the Prophet Muhammad.